Análisis de la producción, comercialización y rentabilidad del cultivo de maíz en el Cantón Mocache. - León Ortíz, Sarahi Pamela (2019)
The objective of this research was to analyze the production, commercialization and profitability of corn cultivation in the Mocache canton, province of Los Ríos, which borders the Quevedo canton to the north, the canton of Vinces to the south, the canton of Ventanas to the east and to the west with the province of Guayas, at an altitude of 120 meters above sea level To this end, a survey was applied to 32 maize producers in the study area, considered as small producers who use all the technologies for their production. Based on the results, it was observed that 75% of the surveyed population indicated that they have been growing maize for 5-6 years, 38% own their own land for corn cultivation. 91% of the farmers stated that the cost of production per hectare ranges between $ 800.00 and $ 1000.00, obtaining an average yield that fluctuates between 97.87 and 126.80 qq / ha showing that there is no sustained growth in yield, and its Productivity is fluctuating from one year to the next. The commercialization is made with the economic dependence of intermediaries in 91% and only 9% do it directly. Profitability ranges between 16.52% and 109.29%, coinciding with the years of lowest and highest cost-benefit ratio. Key words: production, marketing, profitability.